Necessary and Sufficient Conditions for Qualitative Properties of Infinite Dimensional Linear Programming Problems - Khanh, Pham Duy; Mo, Tran Hong; Tran, Trinh T. T. (Numerical functional analysis and optimization, 2019)
Necessary and sufficient conditions for qualitative properties of infinite dimensional linear programing problems such as solvability, duality, and complementary slackness conditions are studied in this article. As illustrations for the results, we investigate the parametric version of Gale's example.